Classism and Everyday Racism as Experienced by Racialized Health Care Users: A Concept Mapping Study - Mahabir, Deb F. (Int J Health Serv, 2021)
In Toronto, Canada, 51.5 % of the population are members of racialized groups. Systemic labor market racism has resulted in an overrepresentation of racialized groups in low-income and precarious jobs, a racialization of poverty, and poor health. Yet, the health care system is structured around a model of service delivery and policies that fail to consider unequal power social relations or racism. This study examines how racialized health care users experience classism and everyday racism in the health care setting and whether these experiences differ within stratifications such as social class, gender, and immigration status. A concept mapping design was used to identify mechanisms of classism and everyday racism. For the rating activity, 41 participants identified as racialized health care users. The data analysis was completed using concept systems software. Racialized health care users reported “race”/ethnic-based discrimination as moderate to high and socioeconomic position-/social class-based discrimination as moderate in importance for the challenges experienced when receiving health care; differences within stratifications were also identified. To improve access to services and quality of care, antiracist policies that focus on unequal power social relations and a broader systems thinking are needed to address institutional racism within the health care system.